Feasibility study on the usage of natural gas for electricity supply at Universiti Malaysia Pahang Gambang campus - Muhammad Zulhilmi, Mohd Ithnin (2012)
Natural gas is one of the energy sources which are more effectives and cheap compare to electricity.The main objective of this thesis is to study the feasibility of natural gas usage as an alternatives energy source to generate electricity to Block Taman Teknologi Industri(TTI) and Block A,B,and C at University Malaysia Pahang (UMP) Gambang Campus.Block TTI is consists of ex-cancelori building and main laboratory of Faculty of Chemical Engineering and Natural Resources (FKKSA) and Faculty of Industrial Science and Technology (FIST).While,Block A,B, and C consists of office buildings,classrooms and lecture hall.There are air conditioner at lecture hall,classroom and offices and also boiler and absorption chiller in laboratory. To support the cost of operation of all these are relatively expensive resulting high electricity bill for UMP every month.This study will compare between the alternatives energy sources which is natural gas with electricity power with the intention of reducing the energy cost.The scopes of this project are to determine the gas consumption and demand,cost for introducing natural gas to the system which consist of piping and construction cost.The method that been used are to construct the economic analysis by using basic financial assessment.SPSS 17.0 software is run for data analysis.From the analysis,it was found that the margin for operational cost of natural gas has significant difference which is lower than operational cost for electricity.The total annual profit,the total annual saving and payback period is also discussed in this paper.The calculation result of economic analysis shows that the introducing natural gas as an alternatives energy source has a good economic benefits.